The role of micro-endodontics in the management of complex root canal anatomy - Almhimeed, Yasser Ali; Ali Aloutaibi, Yaser; Alharbi, Naif Attiah; Althagafi, Fahad Faisal; Saleh Alkarim, Abdulaziz; Benten, Muath Muhammad; Alhefdi, Hatim Mohammed; Aljiaid, Faris Gaze; Alhawsawi, Areej Saleh (International Journal Of Community Medicine And Public Health, 2023)
Micro-endodontics has emerged as a critical component in endodontics, revolutionizing the management of complex root canal anatomy. It utilizes magnification devices, such as dental operating microscopes or loupes, to enhance visualization and identify intricate anatomical details. Micro-endodontics encompasses advanced techniques and technologies that are utilized alongside the principles of conventional endodontics. While both approaches share common goals of cleaning, disinfection, and obturation of the root canal system, micro-endodontics specifically focuses on managing complex root canal anatomy by utilizing specialized tools and techniques to enhance visualization, instrumentation, disinfection, and obturation. Ultrasonic instruments aid in negotiating challenging canal configurations and removing obstructions. Nickel-titanium rotary instruments offer flexibility and durability for efficient cleaning and shaping. Advanced irrigation techniques, such as ultrasonics and laser-activated irrigation, improve disinfection. Innovative obturation techniques ensure the thorough filling of intricate canals. Despite limitations like cost, learning curve, treatment time, and access limitations, micro-endodontics has a promising future. Technological advancements, minimally invasive approaches, biomaterials, biotechnology, artificial intelligence, robotics, and interdisciplinary collaboration will further enhance micro-endodontics, improving treatment outcomes and expanding its scope in complex root canal anatomy.